Der Berufseinstieg von Lehrpersonen Übergang und erste Berufsjahre im Kontext lebenslanger Professionalisierung - Schneider, Klaus (Verlag Julius Klinkhardt, 2021)
In this dissertation, the phases of training, the immediate entry into the profession (induction phase with mentoring) and the further first professional practice of teachers are examined primarily from the perspective of the professional biographical approach (Keller-Schneider & Hericks 2014). The research goal is to identify conditions necessary for both a successful career start and further career development. After grounded theory (Strauss & Corbin 1996), cluster analysis (Buber & Kraler 2000) and qualitative content analysis (Kuckartz 2016), interviews with school leaders and young professionals are analyzed and interpreted using a multimethodological approach. The empirically gained concept is constituted as professionalization through gaining competence, the professional habitualization is established as a way to success. The Habitus concept according to Bourdieu (2015b) with the triad of perception, thinking and acting is at the center of this work and meets the phenomena of uncertainty and contingency (Paseka et al. 2018) with the creative dimension of generating any number of action schemes for any number of situations. The work concludes with the prospect of concrete implementation options for the knowledge gained in the training and further education curricula.